Juvenile justice reform and restorative justice building theory and policy from practice - Bazemore, S. Gordon (Gale virtual reference library, 2005)
Provides an overview of the restorative justice conferencing programs currently in operation in the United States, paying particular attention to the qualitative dimensions of this, based on interviews, focus groups and ethnographic observation.